Neuronal synaptic outputs determine the sexual fate of postsynaptic targets. - Nojima, T.; Kimura, K.; Koganezawa, M.; Yamamoto, D. (Current Biology, 2010)
Synapses mediate inductive interactions for the proper development of pre- and postsynaptic cells: presynaptic electrical activities and synaptic transmission ensure the organization of postsynaptic structures, whereas neurotrophins produced in postsynaptic cells support the survival and enlargement of presynaptic partners. In Drosophila, a motor nerve has been implicated in the induction of the muscle of Lawrence (MOL), the formation of which is male specific and depends on the neural expression of fruitless (fru), a neural sex-determinant gene. Here we report the identification of a single motoneuron essential for inducing the MOL, which we call the MOL-inducing (Mind) motoneuron. The MOL is restored in fru mutant males, which otherwise lack the MOL, if the fru(+) transgene is selectively expressed in the Mind motoneuron by mosaic analysis with a repressible cell marker. We further demonstrate that synaptic outputs from the Mind motoneuron are indispensable to MOL induction, because the blockage of synaptic transmission by shibire(ts) (shi(ts)) during the critical period in development abolished the MOL formation in males. Our finding that sex-specific neurons instruct sexually dimorphic development of their innervating targets through synaptic interactions points to the novel mechanism whereby the pre- and postsynaptic partners coordinately establish their sexual identity.